DataCite Insights: Strengthening Open Science and Research Visibility in Africa (AfricArXiv Open Science Webinar Series) - Mohamad Mostafa (My University, 2026)
Mohamad Mostafa delivered a webinar titled “DataCite Insights: Strengthening Open Science and Research Visibility in Africa”, hosted by AfricArXiv. The session explored how DataCite is advancing Open Science and increasing the global visibility of African research outputs. Mohamad introduced the UNESCO Recommendation on Open Science, outlining its key pillars and their importance for strengthening Africa’s research ecosystem. He provided an overview of DataCite and highlighted the role of the UbuntuNet Alliance DataCite Consortium in supporting regional collaboration and shared PID infrastructure. The webinar featured a practical use case from Ahmed Siyad (SomaliREN), who showcased the Somali National Repository and demonstrated how they are using DataCite infrastructure to improve research discoverability and visibility. The session was moderated by Harold Bowa from the UbuntuNet Alliance. Participants gained valuable insights into PID adoption, repository development, and strategies for building a more open, interoperable, and connected research landscape across Africa.
Keywords: African Research; Open Science; UNESCO Open Science Recommendations; UbuntuNet Alliance; DataCite; Africarxiv; PIDs; Open Metadata